(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Infertility is a global challenge in reproductive health, about 4% to 20% of reproductive-age women are affected with polycystic ovarian syndrome (PCOS).Itis one of the most prevalent endocrine disorders, the underlying principles behind the PCOS development are unknown, and there are no significant therapeutic alternatives or targeted therapeutic interventions towards the disorder. The purpose of this study was to investigate the role of Tinospora cordifolia stem extract and alkaloid rich fraction against PCOS.Method: quantitative real time-polymerase chain reaction (qRT-PCR) was used to assess fold expression. Cell viability was determined by [3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide] MTT assay. Clonogenic (colony formation), Scratch assay were performed and finally, the obtained values were evaluated using ANOVA.Results: Compared with the other ovarian cancer cells, the MTT assay demonstrated that the alkaloid rich fraction had substantial selectivity against SKOV-3 cells. SKOV-3 cells showed low or no toxicity with the extract as well as alkaloid rich fraction. The efficacy of the extract against MCF-7 cells was further validated by migration and clonogenic experiments.Conclusion: CYP17A1 mRNA expressionwas more effectively suppressed in SKOV-3 cells, with a highly significant p-value <0.001. The fold expression of CYP17A1 in SKOV-3 cells after treatment with alkaloid rich fraction was 0.182±0.009. Alkaloid rich fraction inhibits the proliferation of the ovarian cancer cell line SKOV3 than Tinospora cordifolia stem extract, according to the research. Alkaloid rich fraction could be a possible therapeutic androgen antagonist, according to these data, further scientific in-vivo evaluation against metabolic PCOS can be put forth.